Specific Articulation Disorders in Children Native Speakers of Bulgarian – Distribution, Characteristics, Demographic Patterns - Todorova, Ekaterina (European Journal of Social Science Education and Research, 2024)
The article presents a study of the articulation behaviour in 610 Bulgarian children aged 4 years and 5 months up to 7 years and 6 months. In 503 children (82 percent), incorrect articulation of consonant sounds from early, middle and late ontogenesis is established. The highest percentage of non-normative production is registered with sounds of early ontogenesis [l] 79 percent and [r] 43 percent. The percentage distribution of impaired articulation of ontogenetically middle fricatives is 27 percent for the group of [?], [?], [t?] and 20 percent for the group of [s], [z], [ts] respectively. Incorrect articulation of the ontogenetically early sounds [k, g] is recorded in 1 percent of the subjects surveyed for the [k] sound and 4 percent for the [g] sound. What is observed is the presence of age dynamics of impaired articulation where the number of children without disorders tends to increase with age. Another factor of influence on the distribution of the articulation disorders to be noted is the demographic one, i.e. the place of residence. The results obtained show a significant difference in the number of registered articulation disorders in children living in the capital of Bulgaria (Sofia) and living in other places. The established differences are related to the lack of a comprehensivel state policy (health and education) for the organization of prevention, diagnosis and therapy of communicative disorders.